Conceptualizing Cultural Hybridization: A Transdisciplinary Approach - Stockhammer, Philipp (Transcultural Research – Heidelberg Studies on Asia and Europe in a Global Context, 2012)
Within the context of globalization, cultural transformations are increasingly analyzed as hybridization processes. Hybridity itself, however, is often treated as a specifically post-colonial phenomenon. The contributors in this volume assume the historicity of transcultural flows and entanglements; they consider the resulting transformative powers to be a basic feature of cultural change. By juxtaposing different notions of hybridization and specific methodologies, as they appear in the various disciplines, this volume's design is transdisciplinary. Each author presents a disciplinary concept of hybridization and shows how it operates in specific case studies. The aim is to generate a transdisciplinary perception of hybridity that paves the way for a wider application of this crucial concept